Narratives to enhance smoking cessation interventions among African-American smokers, the ACCE project. (December 2015) - Cherrington, Andrea; Williams, Jessica; Foster, Pamela; Coley, Heather; Kohler, Connie; Allison, Jeroan; Kiefe, Catarina; Volkman, Julie; Houston, Thomas
Abstract Background Low-income, African-American smokers are less likely to have resources to aid in quitting smoking. Narrative communication may provide an enhancement to traditional smoking cessation interventions like NRT, medications, or behavioral treatments for this audience. After extensive pilot testing of stories and personal experiences with smoking cessation from African-Americans from a low-income community, we conducted a randomized control trial using stories to augment routine inpatient treatment among African-Americans at an urban Southern hospital (N = 300). Results Differences in smoking cessation outcomes between the intervention (stories DVD + routine clinical treatment) and control (routine clinical treatment) arms were compared using self-report and carbon monoxide measurement at 6-months. Compared to control, individuals who viewed the intervention stories DVD reported greater intentions to quit. Although continuous quitting marginally favored the intervention, our main result did not reach statistical significance (p = 0.16). Conclusion Narrative communication via storytelling to promote smoking cessation among African-Americans in the South is one method to communicate smoking cessation. Results suggest this may not be sufficient as a stand-alone augmentation of routine clinical treatment for continuous smoking cessation. Smoking cessation efforts need to continually assess different means of communicating to smokers about quitting. Clinical Trials Registration: The ClinicalTrials.gov Identifier is NCT00101491. This trial was registered January 10, 2005